How do renewable energy and urbanization cause carbon emissions? Evidence from advanced panel estimation techniques. (February 2022) - Sun, Yunpeng; Li, Haoning; Andlib, Zubaria; Genie, Mesfin G.
Abstract: The Middle East and North African (MENA) economies are highly urbanized and resource-rich economies. However, these economies are under severe threats of climate change. Hence, this study explores the relationships among renewable energy consumption, urbanization, economic growth, and carbon emissions (CE) in the MENA region from 1991 to 2019. This study applies continuously updated fully modified and continuously updated bias-corrected methods and illustrated the presence of the environmental Kuznets curve hypothesis in the long run. Moreover, rapid urbanization and economic growth contributed to higher CE, while renewable energy consumption was found to be the optimal solution to mitigate CE. These results imply that the MENA region is heavily reliant on primary energy consumption, thus, a transition towards green and sustainable energies is imperative to neutralize adverse environmental consequences. Highlights: Renewable energy decreases carbon emissions in the MENA region. Economic growth and urbanization contribute to higher emissions. The empirical results confirm the Environmental Kuznets Curve Hypothesis in the long run for the MENA region.